Professional-Oriented Educational Output In The Teaching Of Chemistry - Qurbonova Muattar Erkinovna (Genius Journals, 2022)
In this article, the main task of pedagogical theory and practice is the formation of a professional worldview of students on the basis of chemical knowledge, its relevance, the methodological foundations of the formation of a professional worldview, the theoretical foundations of the formation of a professional worldview of students on the basis of chemical knowledge
Keywords: professional worldview; worldview; intellectual development; The possibilities of forming a professional worldview based on chemical knowledge